2019
DOI: 10.3389/fphar.2019.00342
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Defunctionalization Supresses Tim-3-Galectin-9 Secretory Pathway in Human Colorectal Cancer Cells and Thus Can Possibly Affect Tumor Immune Escape

Abstract: The Tim-3-galectin-9 secretory pathway is known to protect various types of cancer cells against host immune surveillance. We found that pharmacologically induced mitochondrial dysfunction leads to a reduced galectin-9 expression/exocytosis in human colorectal cancer cells and re-distribution of this protein (the effect described for various cellular proteins) into mitochondria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…On cell assays were employed to detect surface presence of galectin-9 and CD8. We used Li-Cor secondary antibody to recognize anti CD8 primary antibody and then visualized as described before (4, 17).…”
Section: Methodsmentioning
confidence: 99%
“…On cell assays were employed to detect surface presence of galectin-9 and CD8. We used Li-Cor secondary antibody to recognize anti CD8 primary antibody and then visualized as described before (4, 17).…”
Section: Methodsmentioning
confidence: 99%
“…We then tested if naturally occurring, dying cell-derived HMGB1 can induce similar effects in TLR4 expressing cells. We exposed several types of human cancer cell lines (THP-1, Colo 205 and MCF-7) for 24 h to 100 µM BH3I-1 (5-[(4-bromophenyl)methylene]-a-(1-methylethyl)-4-oxo-2-thioxo-3-thiazolidineacetic acid), which is a synthetic cell-permeable Bcl-XL antagonist that induces apoptosis (by inhibiting the interactions between the BH3 domain and Bcl-XL thus defunctionalising mitochondria) ( 23 ). We found that upon stimulation with BH3I-1 THP-1 released the highest amounts of HMGB1 ( Supplementary Figure 7 ).…”
Section: Resultsmentioning
confidence: 99%
“…In agreement with other reports, Chiyo and coworkers demonstrated that Gal-9 induces apoptosis in esophageal squamous cell carcinoma through the mitochondria [ 85 ]. Sakhnevych et al found that Gal-9 and its receptor Tim-3 form a complex and accumulate in the mitochondria in response to a Bcl-X L antagonist in colorectal cancer cells [ 84 ]. Extracellular Gal-7 can reenter cells and translocate into the nucleus to interact with bcl-2 as an anti-apoptosis function to promote breast cancer chemoresistance [ 132 ].…”
Section: The Roles Of Galectins In Cancer Metabolism Reprogrammingmentioning
confidence: 99%
“…Non-peptide compounds, such as OTX008, have been designed to target Gal-1 based on the effect of anginex [ 87 ], which has been found to serve as a therapeutic reagent for cancer and diabetic patients [ 40 , 87 , 182 , 183 , 184 ]. Treatment with BH3I-1 blocks the interaction between Tim-3 and Gal-9, which increases immune surveillance in colorectal cancer [ 84 ]. In addition, plant-derived galactomannans (known as DAVANAT) have been found to bind both Gal-1 and Gal-3, leading to CD8(+) tumor-infiltrating lymphocyte cytotoxicity [ 166 , 185 , 186 ].…”
Section: Available Inhibitors For Targeting Galectinsmentioning
confidence: 99%